Nanofluid enhanced oil recovery using induced ZnO nanocrystals by electromagnetic energy: Viscosity increment - Alnarabiji, M.S. (Elsevier Ltd, 2018)
Extracting the trapped oil in the pores and channels of rock reservoirs, after secondary recovery, using traditional enhanced oil recovery (EOR) techniques is still a challenging task. Nano-materials offer novel pathways to address these unsolved challenges as EOR agents due to their unique characteristics. This study aimed to investigate the novel use of zinc oxide nanocrystals (ZnO-NCs) in EOR and, investigate the influence of the combination of ZnO-NCs with EM energy irradiation on the recovery efficiency. For this purpose, different nanofluid concentrations and flow rates, as well as brine salinity was injected into the porous medium, in the absence of EM energy, to obtain the optimum experimental conditions with the highest recovery efficiency. The injected nanofluid in the porous medium, under the optimum conditions, was subjected to EM energy. The Zinc oxide nanofluid (ZnO-NF) showed a significant rise in recovery efficiency in the absence of EM energy by 50 ROIP due to the self-assembling of the ZnO-NCs which resulted in an increment in the local viscosity of the nanofluid at the waterâoil interface. This study proved the capability of EM energy to enhance the viscosity of the injected ZnO-NF in the porous medium, which consequently increased the recovery efficiency by 23.3 ROIP through the electrorheological effect of the activated dielectric ZnO-NCs. Â© 2018 Elsevier Ltd